Visiting an Urban Park in a Smart City: An Intelligent Systemic Approach Considering Visitors´ Desires and Expectations - Sandoval Chávez, Diego Adiel; Reyes, Aida Yarira (El Colegio de Chihuahua, 2021)
Abstract. Public space is necessary to achieve wellbeing in cities. Urban parks in particular play a decisive role because they provide a connection between urban life and nature. Two case studies regarding the positive role of urban parks are presented in this chapter. The first case study regards a group of visitors driving under the influence looking for a safe port to avoid being the cause of an accident and stopping in a nearby park. The second case focuses on finding the best route for a visitor to avoid allergenic vegetation. In both cases, we adopted a technological approach using a mobile device, geo-referenced systems and biometric identification equipment to locate both the users and the best path to visit the park. We tested both systems at the “Hermanos Escobar” Central Park, located in Juarez, Mexico. The results show that a safe harbor for intoxicated drivers is located near the west entrance. At this location, there is easy access to restrooms and it is a safe place to leave the car overnight. Furthermore, the park is an allergy-free space that is easily walkable, except for the east side of the park—where most of the allergenic species, such as Morus nigra, are concentrated. In this chapter, we present a general discussion of the advantages of both systems and the conclusions derived from this preliminary study. Keywords: Urban green spaces, Smart Cities. Intelligent dispositive to decision support system.